„Nicht Sklavin, sondern Freie“ – Stationen feministischer Theologie 1934 - 1999: Festrede zum 65. Geburtstag von Luise Schottroff in Kassel am 14. Juli 1999 (lectio difficilior, 2000)
Looking back on sixty-five years of history of women in theology in the German-speaking parts of Europe, this speech sums up institutional challenges and hindrances as well as developments and successes in feminist theology and exegesis. While centering on the honoree, Luise Schottroff, it connects her individual biography with the broader history of feminist and liberation theology in Germany, and with the history of both protestant and Roman Catholic churches.